Degradation of desphenyl chloridazon in a novel synergetic electrocatalytic system with Ni–Sb–SnO2/Ti anode and PEDOT/PSS-CNTs modified air diffusion cathode. (1st June 2021) - Zhao, Jingyun; Chi, Zexu; Dong, Heng; Sun, Changfu; Yu, Han; Yu, Hongbing
Abstract: This study explored the depth treatment of desphenly chloridazon (DPC) wastewater by a novel synergetic dual-electrodes electrocatalytic (SDEs) system which consisted of Ni–Sb–SnO2 /Ti anode (NSSTA) and PEDOT/PSS-CNTs modified activated carbon air diffusion cathode (PP-CNTs AC ADC). NSSTA exhibited an enhanced capability to produce reactive oxygen species (·OH and O3 ), its O3 production increased to 6.54 mg/L. PP-CNTs AC ADC was observed to have improved activity of catalyzing oxygen reduction reaction (ORR) with 648.23 mg/L H2 O2 generated. Owing to the synergetic effect of O3 and H2 O2, additional ·OH was obtained in SDEs system through the electro-peroxone reaction. Compared with the single-electrode electrocatalytic (SE) systems, the SDEs system showed superior pesticide degradation performance, higher mineralization current efficiency (MCE) and lower energy consumption (EC). In the SDEs system, the optimal 91.7% of DPC removal efficiency and 90.7% of DPC mineralization efficiency were obtained within 150 min by electrocatalytic oxidation of 17.5 ppm and 25 ppm pesticide wastewater at the current density of 11.94 mA/cm 2, respectively. The treated water showed reduced acute toxicity than that of the raw wastewater, which suggested that the SDEs system is a promising technology for depth treatment of the pesticide industry effluent with simultaneous decontamination and detoxification realized. Graphical abstract: Image 1 Highlights: A SDEs system was established in use of pesticide wastewater depth treatment. Optimal DPC mineralization efficiency of 90.7% was obtained by the SDEs system. The SDEs system was more efficient due to the synergy of the reactive oxidants. Reduced acute toxicity of the treated wastewater guaranteed ecological safety.